Recovery of inspiratory muscle strength in lobectomy patients receiving physical therapy - Kritsnakriengkrai, Sukalya; Vaewthong, Napaporn; Klungthumnium, Jirawat; Kaweemaythee, Thanthai; Sriphol, Pharadorn; Songtanin, Vachiravit; Horbut, Voradorn; Thusombat, Yachuravej (Journal of Medicine and Health Sciences, 2022)
Abstract This study examines evidence of a lack of inspiratory muscle strength after a lobectomy. The purposes of this study are to examine the changes in inspiratory muscle strength after a lobectomy and to compare inspiratory muscle strength between video-assisted thoracoscopic surgery (VATS) and thoracotomy groups. This retrospective study included lobectomy patients who received physical therapy treatment between May 2018 and December 2020 at the Central Chest Institute of Thailand. Maximal inspiratory pressure (MIP) determined inspiratory muscle strength and was investigated at different times: preoperative, postoperative on discharge day, and two weeks after follow-up. The data were analyzed using two-way repeated ANOVA. There were 61 eligible participants who underwent lobectomy via VATS (n=45) or Thoracotomy (n=16). MIP was significantly decreased on discharge day when compared to preoperative values (p<0.001) and was returned to the preoperative level for two weeks follow-up. When comparing between VATS and Thoracotomy, there was no difference in MIP at discharge day and two weeks follow-up. In conclusion, patients undergoing a lobectomy via VATS or Thoracotomy and received physical therapy treatment suffered the same reduction in postoperative inspiratory muscle strength and recovered to preoperative levels within two weeks of follow-up.